New Directions in Children's Welfare Professionals, Policy and Practice - Pinkney, Sharon (Palgrave Macmillan UK, 2018)
This book makes a distinctive contribution to reflections on what child-centred practice means in the complex area of child welfare. With a theoretical framework informed by insights from a number of disciplinary perspectives, the author pays particular attention to psychosocial, emotional, sensory and spatial influences. The book applies its ideas to case studies, in order to reflect on the contemporary landscape of children's services within the UK. The book sets out the way policy and law establish a complex terrain for contemporary child welfare practice. At a time when the government demands clear answers to perceived child protection failings, Pinkney carefully reflects upon the complexity involved in protecting children. This timely re-examination of child welfare will appeal to social work and children's services professionals; policy makers; as well as students and scholars of social work, childhood studies and social policy.